Insulin secretion kinetics from single islets reveals distinct subpopulations. (17th April 2018) - Guruswamy Damodaran, Rajesh; Poussard, Alexandre; Côté, Benoît; Andersen, Parker L.; Vermette, Patrick
Abstract : Type II diabetes progresses with inadequate insulin secretion and prolonged elevated circulating glucose levels. Also, pancreatic islets isolated for transplantation or tissue engineering can be exposed to glucose over extended timeframe. We hypothesized that isolated pancreatic islets can secrete insulin over a prolonged period of time when incubated in glucose solution and that not all islets release insulin in unison. Insulin secretion kinetics was examined and modeled from single mouse islets in response to chronic glucose exposure (2.8‐20 mM). Results with single islets were compared to those from pools of islets. Kinetic analysis of 58 single islets over 72 h in response to elevated glucose revealed distinct insulin secretion profiles: slow‐, fast‐, and constant‐rate secretors, with slow‐secretors being most prominent (ca., 50%). Variations in the temporal response to glucose therefore exist. During short‐term (<4 h) exposure to elevated glucose few islets are responding with sustained insulin release. The model allowed studying the influence of islet size, revealing no clear effect. At high‐glucose concentrations, when secretion is normalized to islet volume, the tendency is that smaller islets secrete more insulin. At high‐glucose concentrations, insulin secretion from single islets is representative of islet populations, while under low‐glucose conditions pooled islets did not behave as single ones. The characterization of insulin secretion over prolonged periods complements studies on insulin secretion performed over short timeframe. Further investigation of these differences in secretion profiles may resolve open‐ended questions on pre‐diabetic conditions and transplanted islets performance. This study deliberates the importance of size of islets in insulin secretion. © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 34:1059–1068, 2018